PCR-based detection and phylogenetic analysis of Candidatus Liberibacter asiaticus in citrus orchards across Nepal - Richa Giri; Bal Kumari Oliya; Siddartha Gautam; Krishna Das Manandhar (PLoS ONE, 2026)
Citrus greening disease, also known as huanglongbing (HLB), is caused by the gram-negative α-proteobacteria Candidatus Liberibacter species. This disease poses a significant threat to citrus production worldwide, including in Nepal. This study aimed to perform the diagnosis and phylogenetic analysis of the citrus greening pathogen in Nepal using both conventional PCR and computational methods. A total of 1,026 citrus leaf samples were collected from thirteen districts across six provinces in the country. PCR-based diagnosis was performed using the primer set Las606/LSS, which targets the 16S rRNA gene of Candidatus Liberibacter asiaticus. The reliability of the PCR was validated by including previously confirmed positive and negative controls in every run. Furthermore, each assay was performed in triplicate to ensure consistency and reproducibility of results. Additionally, 16S rRNA gene sequencing was performed using Sanger sequencing for five samples. The obtained sequences were deposited in GenBank and a phylogenetic tree was constructed based on these sequences. Among the 1,026 samples tested, 255 were positive, indicating the widespread distribution of HLB across Nepal. All consensus sequences from Nepal showed strong evolutionary relatedness within the Ca. L. asiaticus cluster, with over 99% genetic similarity to reference sequences from various parts of the world. Phylogenetic analysis revealed that the Nepalese sequences were closely related to Ca . L. asiaticus sequences from India (Punjab and Meerut) and sequences obtained from different regions of Nepal clustered closely together. The molecular findings from this study reveal a high prevalence of citrus greening disease across Nepal and underscore the urgent need for integrated management policies, including the use of certified clean planting material and vector (psyllid) control programs. The generated sequence data serves as a vital resource for developing regional diagnostic tools and guiding future surveillance strategies to mitigate HLB’s impact on the world’s citrus industry.